Safety of reduced dose of mycophenolate mofetil combined with tacrolimus in living-donor liver transplantation - Kim, Hyeyoung; Yi, Nam-Joon; Lee, Juyeun; Kim, Joohyun; Moon, Mi-Ra; Jeong, Jaehong; Lee, Jeong-Moo; You, Tae Suk; Suh, Suk-Won; Park, Min-Su; Choi, YoungRok; Hong, Geun; et al. (Clinical and molecular hepatology, 2014)
The dose of mycophenolate mofetil (MMF) has been reduced in Asia due to side effects associated with the conventional fixed dose of 2-3 g/day. We aimed to determine the pharmacokinetics of a reduced dose of MMF and to validate its feasibility in combination with tacrolimus in living-donor liver transplantation (LDLT). Two sequential studies were performed in adult LDLT between October 2009 and 2011. First, we performed a prospective pharmacokinetic study in 15 recipients. We measured the area under the curve from 0 to 12 hours (AUC(0-12)) for mycophenolic acid at postoperative days 7 and 14, and we performed a protocol biopsy before discharge. Second, among 215 recipients, we reviewed 74 patients who were initially administered a reduced dose of MMF (1.0 g/day) with tacrolimus (trough, 8-12 ng/mL during the first month, and 5-8 ng/mL thereafter), with a 1-year follow-up. We performed protocol biopsies at 2 weeks and 1 year post-LDLT. In the first part of study, AUC(0-12) was less than 30 mgh/L in 93.3% of cases. In the second, validating study, 41.9% of the recipients needed dose reduction or cessation due to side effects within the first year after LDLT. At 12 months post-LDLT, 17.6% of the recipients were administered a lower dose of MMF (0.5 g/day), and 16.2% needed permanent cessation due to side effects. The 1- and 12-month rejection-free survival rates were 98.6% and 97.3%, respectively. A reduced dose of MMF was associated with low blood levels compared to the existing recommended therapeutic range. However, reducing the dose of MMF combined with a low level of tacrolimus was feasible clinically, with an excellent short-term outcome in LDLT.